Associations between fungal root endophytes and grass dominance in arid highlands. (June 2020) - Menoyo, Eugenia; Teste, François P.; Ferrero, Marcela A.; Lugo, Mónica A.
Abstract: In arid highland environments harsh conditions for vegetation establishment prevail. Plants in these environments develop different strategies to survive, including associations with fungal root endophytes. These associations may improve plant growth, helping plant resistance to adverse environments. The aim of this study was to determine the relationship among arbuscular mycorrhizal fungi (AMF), dark septate endophytes (DSE) and dominance degree of Poaceae in arid highlands of Argentine Puna. We studied AMF and DSE root colonization, and rhizospheric hyphal densities of dominant and subordinate grass species. Dual and positive associations between AMF and DSE prevailed. Dominant grasses had the highest levels of AMF and DSE root colonization. Dominant and intermediate grasses were associated with the highest values of rhizospheric hyphal density. In Puna highlands, the interactions among AMF, DSE and grasses suggest that fungal root endophytes may play a role in structuring grass communities by differentially improving the resistance to harsh conditions. Highlights: Relationships between fungal root endophytes and grass dominance were studied. Dominant grasses had the greatest AMF and DSE root colonization. Positive associations between AMF and DSE root colonization were determined. We emphasize the importance of AMF-DSE extraradical development on plant dominance. Plant-fungal root endophyte associations may determine the plant community structure.